Mamíferos del departamento del Atlántico, Colombia (2020)
We presents the first taxonomic list of wild mammals for the Atlántico department, in the Caribbean coast of Colombia. We recorded 92 species distributed in 11 orders, 37 families, and 74 genera, which represents 16.5 % of the mammal fauna recorded in Colombia. We found three species endemic to Colombia, Cebus versicolor, Saguinus oedipus, and Pattonomys semivillosus, 10 species in some national category of threat, 13 in any global category, and four Data Defficient. The representativeness of mammals is low, compared to other departments in the country, but it might be underestimated, due to low sampling effort and lack of exploration in various areas of the department